Stable Triple Cation Perovskite Precursor for Highly Efficient Perovskite Solar Cells Enabled by Interaction with 18C6 Stabilizer. (9th December 2019) - Wu, Xiayan; Jiang, Yue; Chen, Cong; Guo, Jiali; Kong, Xiangyu; Feng, Yancong; Wu, Sujuan; Gao, Xingsen; Lu, Xubing; Wang, Qianming; Zhou, Guofu; Chen, Yiwang; et al.
Abstract: Triple cation perovskites (Cs0.05 (MA0.17 FA0.83 )0.95 Pb(I0.83 Br0.17 )3 ) have received lots of attention owing to the excellent stability and photovoltaic performance. However, the development toward efficient solar cells has been significantly impeded by its intrinsic precursor instability, as well as defective crystal surface. Herein, a strategy for introducing the additive of 1, 4, 7, 10, 13, 16‐hexaoxacyclooctadecane (18C6) in the precursor solution, rendering an excellent stability of more than one month, and the defect passivation effect on the crystal surface are demonstrated. In those perovskite solar cells, a power conversion efficiency of 20.73% has been achieved with a substantially improved open‐circuit voltage and fill factor. As evidenced by the density functional theory calculations, the fundamental reason relating to the enhanced performance is found to be the interaction effect between the 18C6 and cations, and in particular the formation of the 18C6/Pb complex. This finding represents an alternative strategy for achieving a stable precursor solution and efficient perovskite solar cells. Abstract : A strategy for introducing the additive 1, 4, 7, 10, 13, 16‐hexaoxacyclooctadecane (18C6) into the triple cation perovskite precursor solution is demonstrated, and its influence in precursor and perovskite crystals is thoroughly investigated with simultaneous experimental and theoretical methods. It is found that the formation of the 18C6/Pb complex plays a significant role in the enhanced precursor stability and defect passivation effect within the crystal surface.